Kepemimpinan inovatif dalam pelaksanaan program swasembada pangan nasional di Kabupaten Bone - Ali Anas; Muh Tang Abdullah (Universitas Merdeka Malang, 2021)
The research aims to analyses the innovative leadership capacity in increasing national food self-sufficiency through the direct seed planting program in Bone Regency. Innovative leadership is a crucial dimension in the implementation of an innovation program to increase national food self-sufficiency. In its development innovative leadership capacity can be described through strategic planning, commitment and stability of a leader, these abilities will be described in the implementation of the ATABELA program in Bone District. From the results of the study, it was found that the strategic planning of the Regent as the head of the region was active in disseminating information about the ATABELA innovation program, involving local government stakeholders to realize the vision and mission of the Regent and Deputy Regent in the ATABELA innovation program. these were instructed to the Department of Agriculture, the existence of collaboration in the implementation of innovation ATABELA. In terms of leadership commitment, this research has not been supported by specific regulations in the form of local regulations on innovation, but the leadership commitment appears in the direct seed planting tool innovation program with the legitimacy of a strong Regent and legislative members, the majority of which are in the DPRD from the Golkar party whose chair is also the Regent. also, leadership commitment was found with the Regent's leadership character that was hard and a high willingness to innovate in increasing national food self-sufficiency with direct seed planting programs could be realized. Furthermore, leadership stability in implementing innovation with dedication starting from career officials, becoming a Deputy Regent, expert staff of the Governor of South Sulawesi and eventually being elected as a Regent with capital and experience, then strongly supports ideas and knowledge about the characteristics of the Bone Regency to carry out innovation.